Research at the Conservatorio Vicente Emilio Sojo: An unrepeatable experience (Mayéutica Revista Científica de Humanidades y Artes, 2023)
This essay is based on the testimonial narrative and its purpose is to share the contributions that Maestro Juan Francisco Sans had within the Fundación ConservatorioVicente Emilio Sojo (FCVES), Barquisimeto, Lara state, Venezuela, specifically in the Center for Research and Documentation in terms of local music education and hisknowledge materialized in research products published in the Universalia/Músicas Journal, created by this Center. The closeness with Sans was acquired through thisspace, serving as a vehicle to generate indepth changes in the way of investigating and understanding the musical phenomenon, by questioning the theoretical and methodicalarguments that have sustained musicology and musical research since its beginnings. His reflections will be present throughout this paper, which I write out of eternal affection,appreciation of his important written work and respect for his musical thought.
Keywords: Juan Francisco Sans; Conservatory; Research and Documentation Center; musical research; musicology